Transcriptional and metabolic changes associated to the infection by Fusarium verticillioides in maize inbreds with contrasting ear rot resistance - Campos Bermudez, Valeria Alina; Fauguel, Carolina Maria; Tronconi, Marcos A.; Casati, Paula; Presello, Daniel Alberto; Andreo, Carlos Santiago (2017)
Fusarium verticillioides causes ear rot and grain mycotoxins in maize (Zea mays L.), which are harmful to human and animal health. Breeding and growing less susceptible plant genotypes is one alternative to reduce these detrimental effects. A better understanding of the resistance mechanisms would facilitate the implementation of strategic molecular agriculture to breeding of resistant germplasm. Our aim was to identify genes and metabolites that may be related to the Fusarium reaction in a resistant (L4637) and a susceptible (L4674) inbred. Gene expression data were obtained from microarray hybridizations in inoculated and non-inoculated kernels from both inbreds. Fungal inoculation did not produce considerable changes in gene expression and metabolites in L4637. Defense-related genes changed in L4674 kernels, responding specifically to the pathogen infection. These results indicate that L4637 resistance may be mainly due to constitutive defense mechanisms preventing fungal infection. These mechanisms seem to be poorly expressed in L4674; and despite the inoculation activate a defense response; this is not enough to prevent the disease progress in this susceptible line. Through this study, a global view of differential genes expressed and metabolites accumulated during resistance and susceptibility to F. verticillioides inoculation has been obtained, giving additional information about the mechanisms and pathways conferring resistance to this important disease in maize.